Drug resistance in human melanoma: mechanisms and therapeutic opportunities - Röckmann, Heike; Schadendorf, Dirk (Onkologie, 2003)
In malignant melanoma chemotherapy is very ineffective. This poor prognosis largely results from resistance to conventional chemotherapy. The cellular mechanisms involved in melanoma chemoresistance have yet to be fully elucidated. The relevance of well analyzed drug-resistance mechanisms such as intra-/ extracellular transport, drug-resistance by induction of certain enzyme systems and DNA repair is reviewed. The results of many studies suggest that drug resistance in melanoma is most likely caused by a dysregulation of apoptotic processes. Identification of genes and gene products that are responsible for apoptosis, together with emerging information about the mechanism of action and structures of apoptotic regulatory and effector proteins, has laid a foundation for the discovery of drugs, some of which are now undergoing evaluation in human clinical trails for melanoma treatment. The complexity of the molecular variants involved in signal transduction along apoptotic pathways suggests that the cell may have a variety of possibilities for regulating apoptosis and generating apoptosis deficiency. However, identification of drug resistance mechanisms provides new therapeutic targets to overcome chemoresistance in this and other malignancies.
Gesehen am 25.11.2020